Demystifying and Vindicating Communicative Language Teaching - Ana Clara Sánchez Solarte (Asociación Colombiana de Profesores de Ingles, 2016)
Over the years many future teachers have been captivated with the idea that communicative language teaching (CLT) is the most suitable method for teaching a new language. However, there has been little information on how to adapt this panacea to real classrooms. Theory and practice have not moulded in a smooth way due, in part, to the superficial information that teachers share about the nature of CLT. The goal of this paper is to explore the characteristics of CLT, the misconceptions that have led to inconsistent applications of this approach and to describe briefly the aspects to be taken into consideration when incorporating CLT to an EFL setting.